The Effect of Endophytic bacterial inoculation on Banana, Musa acuminata cv. Lakatan (The Philippine Journal of Crop Science, 2014)
Banana is one of the most popular fruit in the world and is top export commodity in the Philippines. This study aimed to assess the response of banana to endophytic bacterial inoculation (EBI) and to develop a simple technology that farmers can easily adopt. EBI presents multiple positive potential benefits to crops like banana, including increase in plant growth and nitrogen fixing capabilities, and may serve as an alternative to intensive fertilizer use. The first of the two experiments was done to test the effects of EBI on Musa acuminate cv. Lakatan. Of the treatments used, the plants treated with the isolate MUCp 12 were significantly greater in plant height and pseudostem diameter, which was comparable to those treated with inorganic fertilizer treatment. The root dry weight and total dry matter yield were also enhanced significantly, as well as in the total phosphorous and total potassium content of inoculated plants. EBI also significantly increased phosphorous uptake. A second experiment, designed to test the combined effects of EBI and inorganic fertilizer application, was shown to considerably but not significantly enhance plant height. A significant increase in pseudostem diameter was seen most in the treatment with combined 60-60-60 fertilizer and MUCp14 treatment. However, the effect of this treatment was not significantly different from inoculation with isolate MUCp 12 alone and inoculation combined with a lower rate of inorganic fertilizer application. This suggests that inoculation alone can increase pseudostem diameter. Even though isolates MUCp 12 and MUCp 14 increased the shoot dry weight, total dry matter yield, and P content of banana, hen combined with either 30-30-30 or 60-60-60 fertilizer treatments, the effect seemed to be unfavorable. The same observation was seen in the N content when isolate MUCp 12 was used. The improved growth and development of the inoculated plants could be attributed to the production of growth promoting substances by the endophytic bacteria. It is recommended that inoculation with bacterial endophytes should be done during nursery stage for seedling establishment. Proper identification and characterization of the bacterial endophytes and growth promoting substances are highly advised. Further research involving field trials using modified inoculation methods are recommended.